Infectious Diseases and Nanomedicine I First International Conference (ICIDN - 2012), Dec. 15-18, 2012, Kathmandu, Nepal - Adhikari, Rameshwar; Thapa, Santosh (Advances in Experimental Medicine and Biology,, 2014)
The book addresses the interdisciplinary scientific approach for the systemic understanding of connections between major human diseases and their treatment regime by applying the tools and techniques of nanotechnology. It also highlights the interdisciplinary collaborative researches for innovation in Biomedical Sciences. The book is a first volume which presents collection of best papers presented in the First International Conference on Infectious Diseases and Nanomedicine held during Dec. 15-18, 2012 in Kathmandu, Nepal. The book focuses mainly on the topics: emerging infectious diseases; antimicrobial agents, vaccines and immunity; drug design, drug delivery and tissue engineering; and nanomaterials and biomedical materials.